Correlation between missed abortion and insertional translocation involving chromosomes 1 and 7 - Ahmed Husseiny; Neveen Ashaat (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2012)
Background: Missed abortion (Silent miscarriage) is defined as intrauterine fetal death before twenty weeks gestation. One of the most common causes of early missed abortions (before 10 weeks gestation) is cytogenetic abnormalities. Objective: To asses if there is a correlation between chromosomal aberrations (especially in chromosome 7) and missed abortion among at least two generations.Materials and Methods: After exclusion of direct causes of missed abortion, this study included 60 women (the study group) who had first trimestric missed abortion and 30 healthy women who did not suffer from any diseases during their pregnancy and had apparently normal outcome (the control group). All cases were diagnosed; the blood and tissue samples were collected from the mothers and abortuses from the Department of Obstetrics and Gynecology, Maternity Hospital, Ain Shams University. Cytogenetic analyses were performed by using conventional technique and G/T banding techniques and Fluorescence In Situ Hybridization (FISH) analysis with a whole chromosome 7 painting probe (WCP7) and a 7q subterminal probe (7q36, qter), prepared by chromosome micro dissection technique was used for confirming the specific chromosomal abnormality.